Anurans as prey: an exploratory analysis and size relationships between predators and their prey - Toledo, L. F.; Ribeiro, R. S.; Haddad, C. F. B. (Blackwell Publishing, 2007)
The vertebrate predators of post-metamorphic anurans were quantified and the predator-prey relationship was investigated by analysing the relative size of invertebrate predators and anurans. More than 100 vertebrate predators were identified (in more than 200 reports) and classified as opportunistic, convenience, temporary specialized and specialized predators. Invertebrate predators were classified as solitary non-venomous, venomous and social foragers according to 333 reviewed reports. Each of these categories of invertebrate predators was compared with the relative size of the anurans, showing an increase in the relative size of the prey when predators used special predatory tactics. The number of species and the number of families of anurans that were preyed upon did not vary with the size of the predator, suggesting that prey selection was not arbitrary and that energetic constraints must be involved in this choice. The relatively low predation pressure upon brachycephalids was related to the presence of some defensive strategies of its species. This compounding review can be used as the foundation for future advances in vertebrate predator-prey interactions.
Keywords: predation; size relationships; allometry; post-metamorphic anurans